Harvesting contractor production and costs in forest plantations of Argentina, Brazil, and Uruguay - Mac Donagh, Patricio Miguel (2017)
Fil: Mac Donagh, Patricio. Universidad Nacional de Misiones. Facultad de Ciencias Forestales. Manejo Forestal y Desarrollo Sostenible; Argentina.